The Effect of Doubling the Minimum Wage on Employment: Evidence from Russia - Alexander Muravyev; Aleksey Oshchepkov (Institute for the Study of Labor (IZA), 2015)
We take advantage of a natural experiment in the minimum wage setting in Russia to study the employment consequences of large hikes in the minimum wage. In September 2007, the Russian government raised the federal minimum wage from 1,100 to 2,300 Rubles and simultaneously gave the regions the power to set their own minima above the federal threshold. In studying the effect of this reform, we follow the approach proposed by David Card and compare changes in employment rates and other labor market outcomes before and after the hike across regions with different shares of affected workers. We find some evidence of adverse effects of the 2007 hike in the minimum wage on employment. They are mostly visible in lower employment rates among the youth, as well as the increased informalization of employment.
Keywords: J38; J23; 330; minimum wages; unemployment; informal employment; Russia